Risk of hepatitis B infections in Olympic wrestling - Bereket-Yücel, S. (British Journal of Sports Medicine, 2007)
Objective: First, to investigate the prevalence of the hepatitis B virus (HBV) and occult HBV infection (OC-HBV) in Turkish Olympic wrestlers. Second, to examine the relationship between HBV DNA values in sweat and blood.